Word Processing : Using Microsoft Word 2000 or Microsoft Office 2000 - Gilpin, Rebecca; Illustrated by Dodd, Emma (London Usborne, 2001)
Designed to help the complete beginner develop a wide-range of word processing skills, this step-by-step guide takes the user through all the basics, such as writing letters and creating letterheads with simple graphics. Screenshots and jargon-free text make this an accessible guide.
Include Colour Illustrations and Index
Keywords: Word processing